PENGARUH KOHESIVITAS KELOMPOK DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN MELALUI SEMANGAT KERJA SEBAGAI VARIABEL INTERVENING PADA SUTIASA JAMRUD - Charisa Qudsi; widiartanto widiartanto (Jurnal Ilmu Administrasi Bisnis, 2018)
Employee performance is a way of business organization to achieve the aim. Employees who is already hard work and give the best performance, will make the company can take the glory. Group cohesiveness and communication have impact to increase employee performance. Except on those, spirit at work become one of factor to achieve the joy of emploee performance. That is why three of those are imporant and need focus to improve employee performance on Sutiasa Jamrud. Type of research used is Explanatory Research. The sample of research is 74 respondents. The sample was taken using the technique of disproportionate stratified random sampling. The results showed that group cohesiveness and communication significantly influence the spirit at work, which is r = 0.635 with the coefficient of determination of 40.3%. Based on F test, get the result of F count 23,980. The results also showed that group cohesiveness, communication, and spirit at work significantly influence employee performance, which is r = 0,624 with coefficient of determination equal to 62,4%. Based on F test, get result of F count 38,667 which is bigger than F table. Based on the results of the analysis of path shows that the morale variable mediates the cohesiveness of the group and the communication of the employee's performance. The spirit of work mediates partially because either directly or using the mediation variable, morale shows significant results. The suggestion that can be given to Sutiasa Jamrud is that the company should be able to support the employee's attitude to be more united with the group, and the company can provide better communication system so that employees can improve morale so that desired employee performance can be achieved.